1997
DOI: 10.1002/(sici)1097-4628(19970620)64:12<2265::aid-app1>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Blends of polypropylene with poly(cis-butadiene) rubber. I. Phase structure and morphology of blends

Abstract: Pressed films of blends of polypropylene with poly( cis-butadiene) rubbers (PcBR) or grafted copolymer of ethyl acrylate (EA) onto PcBR (PcBR-g-EA) was examined by IR spectra, small angle X-ray scattering, small angle laser scattering (SALS), and scanning election microscopy (SEM). The problem of isomerization on PcBR (or PP/PcBR) is discussed by melt mixing (at a temperature of 180ЊC) using IR. X-ray scattering from the relation of phase was analyzed using Porod's law and led to the values of the interface la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 3 publications
0
13
0
Order By: Relevance
“…In fact, if the blend is compatible or partially compatible system, the transition layer is formed by molecular migration and passes through mutually between two-phase systems [21]. Further, this transition layer often acts to transmit the stress from one phase to the other and the efficiency of stress transfer continuity depends on the nature of the transition layer.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, if the blend is compatible or partially compatible system, the transition layer is formed by molecular migration and passes through mutually between two-phase systems [21]. Further, this transition layer often acts to transmit the stress from one phase to the other and the efficiency of stress transfer continuity depends on the nature of the transition layer.…”
Section: Introductionmentioning
confidence: 99%
“…(18). Thus, the important thing is to determine the value of k. For this purpose, one can first determine the polarization ratio of the two components and calculate c by an experiment under the same condition where Q is known and therefore, obtain k by means of the definition of k.…”
Section: Appendixmentioning
confidence: 99%
“…In fact, when a suitable compatibilizer is added, it will locate between the two immiscible phases, anchor its molecular segments into the homopolymers, and thus form the interface/transition layer. [18] Further, this transition layer often acts to transmit the stress from one phase to the other and the efficiency of stress transfer continuity depends on the nature of the transition layer; in other words, the addition of the compatibilizer can improve the adhesion between phases, and consequently, improve the mechanical properties of blends. However, studies concerning the quantitative analysis of the transition layer are limited.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to them, poly (cis-butadiene) rubber, nonpolar and having excellent elasticity, is easily available and cheaper. Presently, some attention has been played on toughening iPP using PcBR [6][7][8] .…”
Section: Introductionmentioning
confidence: 99%
“…Sheng et al [6] investigated and compared phase structure and morphology of PP=PcBR and PP=PcBR-g-EA blends. They found that the mean size of the dispersed phase in blends of PP with PcBR-g-EA was smaller than that in blends of PP with PcBR.…”
Section: Introductionmentioning
confidence: 99%